Muscle Co‐Activation Across Activities of Daily Living in Individuals With Knee Osteoarthritis. Issue 5 (25th April 2019) - Smith, Stephanie L.; Allan, Richard; Marreiros, Sara P.; Woodburn, James; Steultjens, Martijn P. M.
Abstract : Objective: Muscle co‐activation has been shown to be elevated in individuals with knee osteoarthritis (OA) during gait. Comparisons of muscle co‐activation across different activities of daily living such as stair negotiation have yet to be explored. The aim of this study was to explore muscle co‐activation across different activities of daily living in patients with knee OA. Methods: Muscle co‐activation was assessed in 77 symptomatic knee OA patients (mean ± SD age 62.5 ± 8.1 years, body mass index 29.4 ± 6.0 kg/m 2, and sex 48:29 female:male) using electromyography (EMG), during a series of walking, stair negotiation (ascent, descent), and sit‐to‐walk activities. EMG was recorded from 7 sites, mediolateral gastrocnemius, biceps femoris, semitendinosus, vastus lateralis/medialis, and rectus femoris, and normalized to maximal voluntary isometric contraction. Correlation was used to assess the consistency of co‐activation across activities. Repeated‐measures analysis of variance assessed the muscle combination by activity differences. Results: Muscle co‐activation was highest during stair ascent. When comparing muscle combinations within the same activity, we found that correlations ranged from r = 0.003 to r = 0.897, of which 80% of the combinations were significant. Between activities, muscle co‐activation was significantly different ( P < 0.05). Mediolateral muscle co‐activation was higher than hamstrings/quadriceps across activities. Conclusion: Two muscle co‐activation strategies were observed during activities of daily living in patients with knee OA to maintain stability. Muscle co‐activation was higher during more challenging activities, particularly when the joint was accepting load. Mediolateral muscle co‐activation was higher than hamstrings/quadriceps, so that mediolateral co‐activation was thought to be a stabilization mechanism, while hamstrings/quadriceps co‐activation responds to knee flexion moments, suggesting that different muscle combinations may have different roles in responding to joint demand.